How Much Room Does Latin America and the Caribbean Have for Implementing Counter-Cyclical Fiscal Policies? - Calderón, Cesar; Fajnzylber, Pablo (World Bank, Washington, DC, 2012)
Latin America's government debt has exhibited a clear downward trend since 2003. While this has been partly due to rapidly increasing commodity prices, more sustainable fiscal policies have also been a contributing factor. In effect, in a significant break with the past, cyclically adjusted government balances have raised (fallen) in response to increases (reductions) in debt levels. However, Latin governments have continued to under?save in good times and therefore fiscal policy has remained pro-cyclical, thus weakening the ability to protect the poor and maintain infrastructure investments during bad times. Financing and institutional constraints to more counter?cyclical fiscal policies still remain in most countries. They are lowest in Chile, followed by Brazil and Colombia, and highest in Ecuador and Venezuela. Looking forward, long?term sustainability considerations cannot be ignored as decisions are made regarding the size, composition and targeting of fiscal stimulus packages.